Encouraging Rural Engagement Among Students: Building Career Pathways in the Agricultural Sector - Pranvera Troka; Amalia Tola; Jonida Avdulaj; Marsela Luarasi; Klea Nika (European Scientific Journal, ESJ, 2024)
This study explores the factors influencing the career decisions of students at the Agricultural University of Tirana (AUT), focusing on their motivations, attitudes, and willingness to engage in the agricultural sector. Albania faces significant challenges due to migration, aging farmers, and declining interest in agricultural fields, exacerbating workforce shortages in this critical sector. Using a structured questionnaire administered to 307 students from the Faculty of Economics and Agribusiness at AUT, the study identifies key motivators and barriers that affect students’ career choices. The results show that employment opportunities, personal interest in the field, and financial prospects are the main factors that motivate students to choose a study program in agriculture and related fields. However, a multinomial logistic regression model identifies factors such as year of study, perception, internship, extracurricular activities, career consulting, and level of information about the field as significant determinants of students’ willingness to pursue a career in the agricultural sector after graduation. Factors such as a positive perception of agriculture, participation in internship programs and extracurricular activities, or career consulting from the university influence students to engage and retain within the sector. This study provides valuable data to formulate and develop strategies for attracting students in the agricultural sector. It recommends improving career counseling, providing more practical experiences, and addressing stereotypes to attract and keep young people in agriculture, ensuring the sector’s sustainability in the future.